2002
DOI: 10.1177/10826602015002002
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian Separatist Communities and the Experience of Nature

Abstract: Queer ecology is a cultural, political, and social analysis that interrogates the relations between the social organization of sexuality and ecology. As a part of this analysis, this article explores the ideas and practices of lesbian separatist communities in southern Oregon. It considers that separatists have, since 1974, developed a distinct political-ecological culture to challenge the heterosexual, patriarchal, and capitalist organization of rural North America. Although lesbian separatism was founded on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…In the study of resource extraction and resource dependent communities, there is also increasing attention to the diverse and contradictory gendered interests and identities (e.g. Gibson-Graham, 1994;Reed, 2000Reed, , 2003aSandilands, 2002;Scott, 2007;Mayes and Pini, 2010). However, the attention to feminist theorizing in this particular subsection of rural and environmental scholarship remains comparatively marginal, and much of the work on gender is emanating from disciplines other than the rural and natural resource social sciences, such as cultural studies, feminist labor studies, and women's studies.…”
Section: Natural Resource Scholarship: Why Gender Mattersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of resource extraction and resource dependent communities, there is also increasing attention to the diverse and contradictory gendered interests and identities (e.g. Gibson-Graham, 1994;Reed, 2000Reed, , 2003aSandilands, 2002;Scott, 2007;Mayes and Pini, 2010). However, the attention to feminist theorizing in this particular subsection of rural and environmental scholarship remains comparatively marginal, and much of the work on gender is emanating from disciplines other than the rural and natural resource social sciences, such as cultural studies, feminist labor studies, and women's studies.…”
Section: Natural Resource Scholarship: Why Gender Mattersmentioning
confidence: 99%
“…Correspondingly, the gendered experiences of women in such communities are also likely to vary. Reed (2000Reed ( , 2003a; GibsonGraham (1994); Davis (1993Davis ( , 2000; Tallichet (1995Tallichet ( , 2000; Kafarowski (2005Kafarowski ( , 2009); Sandilands (2002Sandilands ( , 2005 and others have begun to document the nuanced experiences of women with all their variation in places of resource reliance and rural environmental contestations. This paper seeks to highlight this work and build on it with an analytical approach to changing gendered experiences in the context of contemporary resource extraction, which focuses on contradictions in experiences of gender at material and discursive levels.…”
Section: Introductionmentioning
confidence: 99%
“…Histories of lesbian land, of lesbian separatist communities, of efforts to make space for women and a relationship with land, can be considered part of the genealogy of the YWG allotment (Munt, 1998;Sandilands, 2002;Shugar, 1995;Valentine, 1997). Such versions of queer natures are often counters to assumptions that cities offer the appropriate liberatory space for gay politics, against the supposed conservatism of the rural.…”
Section: Queer Natureculturesmentioning
confidence: 99%
“…32 The lesbian separatist pursuit of a feminist rural idyll in the US, recorded by Cate Sandilands and Joyce Cheney, barely touched the Canadian lesbian landscape. 33 Also rare were women-centred semi-rural retreats, such as Cherry Grove in New York State, or the Pagoda in Florida. 34 In Canada, noncensus definitions of the 'rural' fell, in the words of Rachel Torrie, 'somewhere in between the city and the country,' and in documenting the history of rural lesbians in British Columbia she found that they disagreed over who 'qualified as a rural lesbian' because 'rurality was akin to a state of mind'.…”
Section: Outreach Initiativesmentioning
confidence: 99%